Method for improving dyeing fastness of natural dye to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology

Through electrostatic layer self-assembly technology, the deposit of chitosan and phytic acid protective layers on cotton and linen fabrics is solved, and the color fastness and flame retardancy of natural dyes on cotton fabrics is significantly improved. Flame retardant performance.

CN119287687APending Publication Date: 2025-01-10JIANGSU NEW REBA TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411508648.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Natural dyes have low color fastness and flame retardancy on cotton fabrics, resulting in easy fading during daily wear and washing, and insufficient flame retardant performance.

Method used

Using electrostatic layer-based self-assembly technology, by alternately depositing chitosan and phytic acid on the surface of cotton and linen fabrics, a protective layer is formed to improve the adsorption ability and flame retardant properties of the dye. Specific steps include mixing chitosan with citric acid and crosslinking catalyst, pretreating cotton, linen fabric, and dyeing in a natural dye solution, and alternately dipping after dyeing to treat chitosan and phytic acid solutions.

Benefits of technology

The dyeing fastness and flame retardancy of the fabric are significantly improved, the dry friction fastness is increased from level 3 to level 4 to level 5, and the wet friction fastness is increased from level 3 to level 4, while the flame retardancy of the fabric is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005104791220000061
    Figure BDA0005104791220000061
  • Figure BDA0005104791220000062
    Figure BDA0005104791220000062
Patent Text Reader

Abstract

The invention discloses a method for improving dyeing fastness of a natural dye to cotton and linen fabrics based on an electrostatic layer-by-layer self-assembly technology. The method comprises the following steps: (1) carrying out crosslinking treatment on the cotton and linen fabrics by using a chitosan pretreatment solution to obtain pretreated cotton and linen fabrics; (2) dyeing the pretreated cotton and linen fabric by using a natural dye; and (3) respectively placing the dyed cotton and linen fabric in a chitosan pretreatment solution and a phytic acid solution for alternate padding treatment, so that chitosan and phytic acid form a self-assembled fixation protection layer on the surface of the dyed fabric to obtain the high-color-fastness dyed cotton and linen fabric. According to the method for improving the dyeing fastness of the natural dye to the chitosan-darkening cotton and linen fabric based on the electrostatic layer-by-layer self-assembly technology, a certain number of layers of chitosan / phytic acid color fixing protection layers are subjected to electrostatic layer-by-layer self-assembly on the surface of the cotton and linen fabric dyed by the chitosan-darkening natural dye, so that the dyed cotton and linen fabric has high color fastness and flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for improving the dyeing fastness of natural dyes to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology, and belongs to the technical field of dyeing and finishing. Background Art

[0002] Dyeing has the advantages of simple and stable process, energy saving, and shortened process. In addition, it also has a unique style, such as obvious washing feeling and distinct three-dimensional sense. Natural dyes come from natural resources such as plants, insects, animals and microorganisms, and are renewable and sustainable dyes. Natural dyes are widely used in textile dyeing and textile functional finishing due to their low or non-toxicity, good ecological compatibility, and wide sources. Most natural dyes have high color fastness on protein fibers such as silk and wool. This is because protein fibers contain more reactive groups such as amino and carboxyl groups. The amino group carries a positive charge in the dye solution, making it easy for negatively charged natural dyes to adsorb and dye.

[0003] Cotton fabrics are made of cotton fibers and have many advantages, such as being comfortable to wear, good moisture absorption, soft and warm, easy to dye, resistant to washing, and good breathability. However, the main component of cotton fiber is cellulose, accounting for more than 90% of the total weight, of which the reactive groups are usually only hydroxyl groups, of a single type, with weak reactivity, lack of positively charged groups, and low affinity with natural dyes, resulting in low color fastness of natural dyes on cotton fabrics. Cotton fabrics dyed with natural dyes are prone to fading during daily wear and washing, and cannot meet good wearing performance standards. On the other hand, cotton fabrics are flammable, and it is crucial to hinder the spread of fire in textiles during a fire, and their flame retardant properties are also extremely critical.

[0004] The amino groups in chitosan macromolecules are positively charged. When applied to cellulose fibers, they can reduce the Coulomb repulsion of the negative charges on the fiber surface to the dye anions during the dyeing process, increase the dye uptake, and thus have a good deepening effect on anionic dyes such as acid dyes and reactive dyes. Theoretically, natural dyes are anionic dyes, and chitosan can also promote the dyeing depth of anionic pigments on cotton fabrics. However, experiments have found that chitosan does not have a good effect on natural dyes dyeing cotton fabrics. Natural dyes do not dye cotton fabrics deeply, and the dyed cotton fabrics have problems such as poor color fastness. In addition, chitosan is often used as an environmentally friendly synergistic flame retardant to improve the flame retardant properties of textiles. Chitosan is rich in cationic amino groups and can be deposited on the surface of textiles through ionic bonds with anionic groups. As Guan Chongsheng et al. explained in the journal article "Study on Chitosan / Sodium Alginate Coating and Flame-Retardant Polyester Fabric", the flame retardancy of polyethylene terephthalate fabric can be improved by applying a flame retardant coating to the fabric using chitosan and sodium alginate through layer-by-layer self-assembly technology. However, the efficiency of the flame retardant coating is poor, and usually more layers need to be stacked to achieve a significant improvement in flame retardancy. Moreover, more layers of flame retardant finishing often lead to a worse feel of the fabric.

[0005] Therefore, a new and simple dyeing and finishing method is needed to improve the color fastness and flame retardancy of natural dyes on cotton fabrics. Summary of the invention

[0006] In view of the above problems, the purpose of the present invention is to provide a method for improving the color fastness of natural dyes to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology, so as to solve the problems of poor color fastness and poor flame retardancy of natural dyes to cotton fabrics in the prior art.

[0007] To achieve the above-mentioned purpose, the present invention first provides a method for improving the color fastness of natural dyes to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology, comprising the following steps:

[0008] (1) placing chitosan in water, stirring to dissolve it, adding citric acid solution, adding a cross-linking catalyst and water, and stirring at a speed of 500 rpm to mix them evenly to obtain a chitosan pretreatment solution;

[0009] (2) placing cotton or linen fabric into the chitosan pretreatment solution obtained in step (1) to obtain pretreated cotton or linen fabric after pretreatment;

[0010] (3) adding the pretreated cotton or linen fabric obtained in step (2) into a natural dye solution for dyeing to obtain cotton or linen fabric dyed with a natural dye;

[0011] (4) The dyed cotton or linen fabric is placed in a chitosan pretreatment solution and a phytic acid solution for alternate padding treatment to obtain a flame-retardant cotton or linen fabric with high color fastness.

[0012] In one embodiment of the present invention, in step (1), the cross-linking catalyst comprises at least one of sodium hypophosphite, sodium hypophosphite and hypophosphorous acid, and the concentration of the cross-linking catalyst is 1-20 g / L, more preferably 1-10 g / L.

[0013] In one embodiment of the present invention, in step (1), the concentration of the citric acid solution is 1-100 g / L, more preferably 10-50 g / L, and the pH of the solution is adjusted to 3-6 after the citric acid solution is added.

[0014] In one embodiment of the present invention, in step (1), the concentration of the chitosan pretreatment solution is 1-50 g / L, more preferably 5-20 g / L.

[0015] In one embodiment of the present invention, in step (2), the pretreatment process of the cotton or linen fabric comprises: padding the cotton or linen fabric in a chitosan pretreatment solution for 1-3 times, with a padding rate of 100%, drying at 80°C for 3 minutes, and baking at 150°C for 1-3 minutes to obtain the pretreated cotton or linen fabric.

[0016] In one embodiment of the present invention, the natural dye comprises at least one of hematoxylin, madder, cochineal, safflower, onion peel, gardenia, turmeric, and lac insect.

[0017] In one embodiment of the present invention, in step (3), the preparation process of the natural dye solution is: the natural dye is fully dissolved in a citric acid solution with a pH of 3-6 to obtain a dye solution, and the concentration of the dye solution is 2 g / L.

[0018] In one embodiment of the present invention, in step (3), the dye is 0.01-30% (owf) of the fabric weight during dyeing, more preferably 1%-10% (owf), and the bath ratio is 1:50.

[0019] In one embodiment of the present invention, in step (3), the dyeing process is as follows: the dyeing temperature is 20-90° C., the dyeing time is 10-60 min, and the dyeing is followed by washing and drying to obtain cotton and linen fabrics dyed with natural dyes.

[0020] In one embodiment of the present invention, in step (4), the concentration of the phytic acid solution is 10-100 g / L, more preferably 10-50 g / L, and the pH value is adjusted to 3-6 using sodium hydroxide.

[0021] In one embodiment of the present invention, the padding treatment process of the chitosan pretreatment solution and the phytic acid solution after dyeing is that the cotton and linen fabrics are alternately padded in the chitosan pretreatment solution and the phytic acid solution for 1-3 times, with a padding rate of 100%, dried at 80°C for 3 minutes, and baked at 150°C for 1-3 minutes to obtain flame-retardant cotton and linen fabrics with high color fastness.

[0022] Beneficial effects:

[0023] (1) The present invention deposits chitosan and phytic acid protective layers on the surface of chitosan pretreated and dyed fabrics in sequence through electrostatic layer-by-layer self-assembly technology, which can significantly increase the color fastness and flame retardancy of the fabrics. The selection of phytic acid has a significant improvement effect on the color fastness of dyed fabrics.

[0024] (2) Chitosan is first deposited on the surface of the dyed fabric, and then phytic acid is deposited, so that the chitosan coating can better adhere to the surface of the dyed fabric, further improving the color fastness of the fabric.

[0025] (3) Increasing the number of chitosan and phytic acid coating layers helps to further increase the dyeing fastness of the fabric and greatly improves the flame retardancy of the fabric. The dry friction fastness of the fabric increases from level 3-4 to level 4-5, and the wet friction fastness increases from level 3 to level 4, which is a major breakthrough in this field. DETAILED DESCRIPTION

[0026] The outstanding advantages and remarkable features of the present invention are further described below by implementing examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0027] Example 1

[0028] A method for improving the color fastness of natural dyes to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology, comprising the following steps:

[0029] 1g of chitosan powder was placed in 50mL of deionized water, the pH was adjusted to 4 with 10g / L of citric acid, 10mL of 5g / L sodium hypophosphite was added as a cross-linking catalyst, water was added until the pretreatment solution was 100g, and the solution was stirred at 500rpm to obtain a 10g / L chitosan pretreatment solution; 2g of cotton fabric was placed in the chitosan pretreatment solution, double-immersed and double-rolled, the rolling rate was 100%, pre-baked at 80℃ for 3min, and baked at 150℃ for 3min to obtain citric acid cross-linked chitosan pretreated cotton fabric.

[0030] 0.2 g of hematoxylin dye was fully dissolved in 100 mL of citric acid solution with a pH of 4, the dye solution concentration was 2 g / L, and the dyeing was carried out at a constant temperature of 60° C. for 30 min with a bath ratio of 1:50 and a dye to fabric weight of 10% (owf). The dyed cotton fabric was washed and dried to obtain a dyed cotton fabric.

[0031] The dyed cotton fabric was placed in a 10 g / L chitosan pretreatment solution with a pH of 4, immersed and rolled, with a rolling rate of 100%, pre-baked at 80°C for 3 min, and baked at 150°C for 3 min to obtain cotton fabric A1, and its color fastness and limiting oxygen index LOI value were tested.

[0032] Example 2

[0033] A method for improving the color fastness of natural dyes to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology, comprising the following steps:

[0034] 1 g of chitosan powder was prepared and placed in 50 mL of deionized water. The pH value was adjusted to 4 with 10 g / L of citric acid. 10 mL of 5 g / L sodium hypophosphite was added as a cross-linking catalyst. Water was added to 100 g of the pretreatment solution. The solution was stirred at 500 rpm to obtain a 10 g / L chitosan pretreatment solution. 2 g of cotton fabric was placed in the chitosan pretreatment solution, double-immersed and double-rolled with a rolling rate of 100%, pre-baked at 80°C for 3 min, and baked at 150°C for 3 min to obtain citric acid-crosslinked chitosan pretreated cotton fabric.

[0035] 0.2 g of hematoxylin dye was fully dissolved in 100 mL of citric acid solution at pH = 4, the dye solution concentration was 2 g / L, constant temperature shaking dyeing was carried out at 60°C for 30 min, the bath ratio was 1:50, the dye was 10% (owf) to the fabric weight, and the dyed cotton fabric was obtained after washing and drying.

[0036] The dyed cotton fabric was placed in a 50 g / L phytic acid solution with a pH of 4, immersed and rolled, with a rolling rate of 100%, pre-dried at 80° C. for 3 min, and baked at 150° C. for 3 min to obtain cotton fabric A2, and its color fastness and limiting oxygen index LOI value were tested.

[0037] Example 3

[0038] A method for improving the color fastness of natural dyes to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology, comprising the following steps:

[0039] 1g of chitosan powder was prepared and placed in 50mL of deionized water, the pH was adjusted to 4 with 10g / L of citric acid, 10mL of 5g / L sodium hypophosphite was added as a cross-linking catalyst, water was added to 100g of the pre-treatment solution, and the solution was stirred at 500rpm to obtain a 10g / L chitosan pre-treatment solution; 2g of linen fabric was placed in the chitosan pre-treatment solution, immersed and rolled with a rolling rate of 100%, pre-baked at 80°C for 3min, and baked at 150°C for 3min to obtain citric acid cross-linked chitosan pre-treated linen fabric.

[0040] 0.2 g of hematoxylin dye was fully dissolved in 100 mL of citric acid solution at pH = 4, the dye solution concentration was 2 g / L, constant temperature shaking dyeing was carried out at 60°C for 30 min, the bath ratio was 1:50, the dye was 10% (owf) to the fabric weight, and the dyed cotton fabric was obtained after washing and drying.

[0041] The dyed cotton fabric is placed in a 10 g / L chitosan pretreatment solution with a pH of 4, and immersed and rolled with a rolling rate of 100% to obtain the chitosan-fixed dyed cotton fabric.

[0042] The dyed cotton fabric was placed in a 50g / L phytic acid solution with a pH of 4, immersed and rolled, with a rolling rate of 100%, pre-dried at 80°C for 3 min, and baked at 150°C for 3 min to obtain a flame retardant cotton fabric A3 with high color fastness, and its color fastness and limiting oxygen index LOI value were tested.

[0043] Example 4

[0044] A method for improving the color fastness of natural dyes to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology, comprising the following steps:

[0045] 1g of chitosan powder was prepared and placed in 50mL of deionized water, the pH was adjusted to 4 with 10g / L of citric acid, 10mL of 5g / L sodium hypophosphite was added as a cross-linking catalyst, water was added to 100g of the pre-treatment solution, and the solution was stirred at 500rpm to obtain a 10g / L chitosan pre-treatment solution; 2g of linen fabric was placed in the chitosan pre-treatment solution, immersed and rolled with a rolling rate of 100%, pre-baked at 80°C for 3min, and baked at 150°C for 3min to obtain citric acid cross-linked chitosan pre-treated linen fabric.

[0046] 0.2 g of hematoxylin dye was fully dissolved in 100 mL of citric acid solution at pH = 4, the dye solution concentration was 2 g / L, constant temperature shaking dyeing was carried out at 60°C for 30 min, the bath ratio was 1:50, the dye was 10% (owf) to the fabric weight, and the dyed cotton fabric was obtained after washing and drying.

[0047] The dyed cotton fabric is placed in a 10 g / L chitosan pretreatment solution with a pH of 4, and immersed and rolled with a rolling rate of 100% to obtain the chitosan-fixed dyed cotton fabric.

[0048] The dyed cotton fabric was placed in a 50 g / L phytic acid solution with a pH of 4, and then immersed and rolled, with a rolling rate of 100%.

[0049] Continue to alternately immerse in the chitosan solution and the phytic acid solution for a total of 5 times, pre-bake at 80°C for 3 min, and bake at 150°C for 3 min to obtain a flame-retardant cotton fabric A4 with high color fastness, and test its color fastness and limiting oxygen index LOI value.

[0050] Comparative Example 1:

[0051] Prepare 1g of chitosan powder, place it in 50mL of deionized water, adjust the pH to 4 with acetic acid, add water to 100g of the pretreatment solution to obtain 10g / L chitosan pretreatment solution; take 2g of cotton fabric and place it in the chitosan pretreatment solution, double dip and double rolling, the rolling rate is 100%, pre-bake at 80℃ for 3min, and bake at 150℃ for 3min to obtain chitosan pretreated cotton fabric.

[0052] The hematoxylin dye was fully dissolved in citric acid solution, the pH was adjusted to 4, the dyeing was carried out at 60°C for 30 minutes, and the dyed cotton fabric A5 was obtained. The color fastness and limiting oxygen index LOI value were tested.

[0053] Comparative Example 2

[0054] A method for improving the color fastness of natural dyes to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology, comprising the following steps:

[0055] 1g of chitosan powder was prepared and placed in 50mL of deionized water, the pH was adjusted to 4 with 10g / L of citric acid, 10mL of 5g / L sodium hypophosphite was added as a cross-linking catalyst, water was added to 100g of the pre-treatment solution, and the solution was stirred at 500rpm to obtain a 10g / L chitosan pre-treatment solution; 2g of linen fabric was placed in the chitosan pre-treatment solution, immersed and rolled with a rolling rate of 100%, pre-baked at 80°C for 3min, and baked at 150°C for 3min to obtain citric acid cross-linked chitosan pre-treated linen fabric.

[0056] 0.2 g of hematoxylin dye was fully dissolved in 100 mL of citric acid solution at pH = 4, the dye solution concentration was 2 g / L, constant temperature shaking dyeing was carried out at 60°C for 30 min, the bath ratio was 1:50, the dye was 10% (owf) to the fabric weight, and the dyed cotton fabric was obtained after washing and drying.

[0057] The dyed cotton fabric is placed in a 10 g / L chitosan pretreatment solution with a pH of 4, and immersed and rolled with a rolling rate of 100% to obtain the chitosan-fixed dyed cotton fabric.

[0058] The dyed cotton fabric was placed in a 50 g / L sodium tripolyphosphate solution with a pH of 4, and then immersed and rolled, with a rolling rate of 100%.

[0059] Continue to alternately immerse in chitosan solution and sodium tripolyphosphate solution for a total of 5 times, pre-bake at 80°C for 3 min, and bake at 150°C for 3 min to obtain flame-retardant cotton fabric A6 with high color fastness, and test its color fastness and limiting oxygen index LOI value.

[0060] The dry and wet rubbing color fastness of Examples 1-4 and Comparative Examples 1-2 were evaluated according to GB / T 3920-2008 “Textiles - Tests for Color Fastness - Color Fastness to Rubbing”.

[0061] Table 1 Color fastness to rubbing of Examples 1-4 and Comparative Examples 1-2

[0062]

[0063] The flame retardant properties of Examples 1-4 and Comparative Example 1 were evaluated, and the limiting oxygen index was tested on a FTT0080 automatic oxygen index instrument with reference to GB / T5454-2008 "Oxygen Index Method for Combustion Performance Test of Textiles".

[0064] Table 2 LOI values ​​of Examples 1-4 and Comparative Examples 1-2

[0065]

[0066] Compared with dyed fabrics darkened with chitosan alone, the friction color fastness of cotton and linen fabrics dyed with natural dyes based on electrostatic layer-by-layer self-assembly can be increased by 0.5 to 1 level, and the color fastness is significantly improved. However, when the number of assembled layers on the fabric surface reaches 5, the fabric feels hard, and it can be considered for use in specific decoration and other application scenarios. At the same time, its limiting oxygen index LOI value indicates that it can self-extinguish when ignited in the air, which improves the color fastness of the fabric while giving it better flame retardant properties.

[0067] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for improving the color fastness of natural dyes to cotton and linen fabrics based on electrostatic layer-by-layer self-assembly technology, characterized in that: The method comprises the following steps: (1) placing chitosan in water, stirring to dissolve it, adding citric acid solution, adding a cross-linking catalyst and water, and stirring at 500 rpm to mix them evenly to obtain a chitosan pretreatment solution; (2) placing cotton or linen fabric into the chitosan pretreatment solution obtained in step (1) to obtain pretreated cotton or linen fabric after pretreatment; (3) adding the pretreated cotton or linen fabric obtained in step (2) into a natural dye solution for dyeing to obtain cotton or linen fabric dyed with a natural dye; (4) The dyed cotton or linen fabric is placed in a chitosan pretreatment solution and a phytic acid solution for alternate padding treatment to obtain a flame-retardant cotton or linen fabric with high color fastness.

2. The method according to claim 1, characterized in that: In step (1), the cross-linking catalyst includes at least one of sodium hypophosphite, sodium hypophosphite, and hypophosphorous acid, and the concentration of the cross-linking catalyst is 1-20 g / L.

3. The method according to claim 1, characterized in that In step (1), the concentration of the citric acid solution is 1-100 g / L, and the pH of the solution is adjusted to 3-6 after the citric acid solution is added.

4. The method according to claim 1, characterized in that In step (1), the concentration of the chitosan pretreatment solution is 1-50 g / L.

5. The method according to claim 1, characterized in that In step (2), the pretreatment process of the cotton and linen fabric comprises: padding the cotton and linen fabric in a chitosan pretreatment solution for 1-3 times, with a padding rate of 100%, drying at 80°C for 3 minutes, and baking at 150°C for 1-3 minutes to obtain the pretreated cotton and linen fabric.

6. The method according to claim 1, characterized in that The natural dye comprises at least one of hematoxylin, madder, cochineal, safflower, onion peel, gardenia, turmeric and lac insect. The preparation process of the natural dye solution is as follows: the natural dye is fully dissolved in a citric acid solution with a pH value of 3-6 to prepare a dye solution, and the concentration of the dye solution is 2g / L.

7. The method according to claim 1, characterized in that In step (3), the dye is used in an amount of 0.01-30% (owf) of the fabric during dyeing, and the bath ratio is 1:

50.

8. The method according to claim 1, characterized in that In step (3), the dyeing process is as follows: the dyeing temperature is 20-90°C, the dyeing time is 10-60 minutes, and the dyeing is followed by washing and drying to obtain cotton and linen fabrics dyed with natural dyes.

9. The method according to claim 1, characterized in that: In step (4), the concentration of the phytic acid solution is 10-100 g / L, and the pH value is adjusted to 3-6 using sodium hydroxide.

10. The method according to claim 1, characterized in that The padding process of the chitosan pretreatment solution and the phytic acid solution after dyeing is that the cotton and linen fabrics are alternately padded in the chitosan pretreatment solution and the phytic acid solution for 1-3 times, with a padding rate of 100%, dried at 80°C for 3 minutes, and baked at 150°C for 1-3 minutes to obtain flame-retardant cotton and linen fabrics with high color fastness.